IMPLIKASI FAKTOR PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN - Kotimah; Junia Ariyanti Prastiwi; Cep Huda (Jurnal Ilmiah Ekonomi Syariah, 2024)
This research aims to find out how consumer behavior factors can influence consumer purchasing decisions on a product. The background of this research is the increasingly complex factors that exist that can have a certain influence on consumers in deciding to make a purchase of a particular product. This type of research is qualitative research using the literature study method by reviewing several related sources. The results showed that not all factors have the same influence on consumer decisions in buying an item, where several factors have a separate influence on certain products.